Система сплайнів класу C^q (R^2), які є R-функціями двох змінних - Литвин, О. М. (НТУ "ХПІ", 2012)
Запропоновано і досліджено повну систему R-функцій двох змінних, істотно належних до класу C^q (R^2), що складається з R-кон’юнкції. Ці R-функції є поліноміальними сплайнами дефекту 1. Вони є розв’язками системи рекурентних крайових задач для рівняння Пуассона, права частина яких теж є деякою R-функцією з меншим номером q

Full system of the R  functions of two variables essentially belonging to a class C^q (R^2) is offered and investigated. This system consists from R-conjunction alternation. These R-functions are polynomial splines of the degree defect of these splines is 1. The offered R-functions are the solutions the recurrently system of the boundary value problems for the Poisson’s equation. Right part in these Poisson’s equations are also R-functions with smaller number q
Keywords: рівняння границь; рекурентна побудова; підобласті; система функцій; доведення; квадранти